Isak Dinesen's Ecological Power - Mortensen, Peter, (Literature and Cultural Studies E-Books Online, Collection 2026., 2025)
Danish writer Isak Dinesen/Karen Blixen (1885-1962) was colonial plantation manager, big-game hunter, animal rights activist, nature conservationist, flower gardener, and much more. Most importantly, Dinesen wrote thought-provoking, mind-bending, boundary-shifting tales that can help us think constructively and creatively about many facets of life on our troubled planet. Isak Dinesen's Ecological Power reexamines Dinesen in the context of 21st-century debates about time, animals, plants, masculinity, families, the idea of nature, and the very question of what it means to be human in a more-than-human world. We urgently need to power our societies and imaginations in new ways, and this book reconsiders Dinesen's stories as an inexhaustible and so-far largely untapped source of ecocultural energy.